Impact of maternal diet and pregnancy type on the abundance of zoonotic bacteria (Firmicutes and Proteobacteria) in sheep feces and wool - Gallardo Paffetti, Maria; Azócar-Aedo, Lucía; Parra-Vizcaíno, Angel; Larraín, José M.; Díaz, Adriano (Frontiers in Animal Science, 2025)
The large intestine healthy microbiota in sheep hosts pathogenic, but mainly nonpathogenic bacteria, which are essential to intestinal metabolism, contributing energy, antigens, and metabolites that positively impact host physiology, immunity, and metabolism. However, this microbiota also poses a public health risk due to fecal contamination in animal products, such as wool. This study examined how maternal diet and pregnancy type influence the relative abundance of zoonotic bacterial DNA belonging to phyla Firmicutes and Proteobacteria in sheep feces and wool. In total, 18 Ile de France ewes, with 8 carrying twins and 10 single lambs, were divided into two groups: one fed ad libitum on naturalized pasture, the other given red clover hay plus lupine, from 45 days prepartum to 60 days postpartum. Both fecal and wool samples were collected from ewes and lambs four and three times, respectively, and analyzed via qPCR for Firmicutes (Clostridium perfringens type C, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus uberis, Enterococcus faecalis, and Streptococcus agalactiae) and Proteobacteria (Salmonella typhimurium and Escherichia coli serotype O157). Data were analyzed using repeated measures two-way ANOVA. Results showed lower bacterial abundance in fecal samples than in wool samples, with ewe’s wool exhibiting a lower bacterial abundance compared with lamb’s wool. E. faecalis (Firmicutes) and E. coli (Proteobacteria) were the most prevalent bacteria, suggesting environmental contamination related to sheep behavior. In summary, handling offspring from birth to weaning and ewes until 60 days postpartum may increase zoonotic pathogen transmission risk, raising public health concerns regarding exposure to intestinal pathogenic bacteria.